RETRACTED: Effect of supplemental parenteral nutrition on all-cause mortality in critically Ill adults: A meta-analysis and subgroup analysis - Li, Peng; Zhong, ChunYan; Qiao, ShiBin; Liu, JunJun (Frontiers in Nutrition, 2022)
Objective Several observational studies have demonstrated that increased nutritional delivery by supplementary parenteral nutrition (SPN) plus enteral nutrition (EN) reduces the rate of all-cause mortality in critically ill patients. Therefore, we aimed to compare and evaluate the effect of SPN plus EN on all-cause mortality in critically ill adults. Methods Randomized controlled trials were retrieved from PubMed, Embase, Google Scholar, Cochrane Library, and SinoMed (up to May 2021). Adults with severe illness treated with SPN plus EN or with EN alone were enrolled. The risk of bias was evaluated using the Newcastle–Ottawa scale, and meta-analysis was conducted using Stata software. The primary outcome was all-cause mortality and was evaluated by pooled odds ratio (OR). Required information size was also calculated using trial sequential analysis. Results We identified 10 randomized controlled trials, with a total of 6908 patients. No significant differences in rate of all-cause mortality [OR=0.96, 95% confidence interval (CI): 0.84–1.09, P=0.518], ICU mortality (OR=0.90, 95% CI: 0.75–1.07, P=0.229) and hospital mortality (OR=0.95, 95% CI: 0.82–1.10, P=0.482) were found between the SPN plus EN and EN alone groups. SPN plus EN support was associated with a significantly decreased risk of infection (OR=0.83, 95% CI: 0.74–0.93, P=0.001), although duration of mechanical ventilation [standardized mean difference (SMD)=0.20], length of hospital stay (SMD=0.12) and ICU stay (SMD=0.57) were similar between the two groups (all P>0.05). Meta-regression analyses showed no significant correlations between all-cause mortality and baseline clinical factors, including patients’ age, APACHE II score, time of SPN initiation, and follow-up duration (all P>0.05). Subgroup analysis showed that SPN plus EN support was associated with a trend toward decreased rate of all-cause mortality in studies with follow-up <30 days (OR=0.61, 95% CI: 0.36–1.02, P=0.058). Trial sequence analysis showed that the required information size for all-cause mortality was 16 972, and the cumulative Z curve indicated no significant differences in the risk of all-cause mortality between the two groups (P>0.05). Conclusions SPN plus EN support can significantly reduce the risk of infection, although it has no significant effect on all-cause mortality among critically ill patients. More studies are warranted to confirm these findings.